Produtividade da soja inoculada com duas espécies de bactérias e benefícios à pastagem em sucessão - Vicente, Elcio Ricardo José de Sousa (2019)
Improvement of soil microbiology and the use of biological products via sowing, seed or leaf furrows, allied to the correct crop treatment can contribute to higher soybean yields. The objective of this work was to evaluate the effect of co-inoculation using Azospirillum brasilense and Bradyrhizobium japonicum on soybean as well as on Urocloa brizantha syn pasture. brachiaria brizanta cv. Marandu in succession. The experiment was conducted at the Experimental Farm of the University of West Paulista (UNOESTE). The experimental design was in randomized blocks in a 5x2 factorial scheme in a split plot scheme with four replications. The main treatments in the plot consisted of a control (cont - control) and four combinations of inoculants (B-Su - Bradyrhizobium japonicum in the furrow, B-Se - Bradyrhizobium japonicum in the seed, B + A-Se - Bradyrhizobium japonicum + Azospirillum brasilense in the seed, B + A-Su - Bradyrhizobium japonicum + Azospirillum brasilense in the furrow). The subplot is constituted with and without the foliar application of Bradyrhizobium japonicum applied at the V4 phenological stage. Soybean cultivation was conducted by two agricultural harvests, followed by the implementation of pasture in succession. In soybean, the evaluations were: leaf analysis, yield components and yield. In the pasture phase it was evaluated: forage dry mass yield and bromatological composition. The data obtained were submitted to the SISVAR statistical program, and the averages were compared by Tukey test at 5% probability. There was a difference in the number of soybean pods per plant, when the inoculant Bradyrhizobium japonicum was used via sowing furrow plus leaf inoculation at 30 DAE, only in the first crop year. There was an increase in yield of DM Kg ha-1, compared to the same treatments that did not receive application by leaf, referring to the two agricultural years proving the viability of using the inoculation forms used. From the observed data it can be concluded that the yield and yield components of soybean with and without leaf application were different for the control and B-Su treatments, assuming higher value for leaf application of Bradyrhizobium japonicum. Coinoculation influenced the DM productivity of marandu grass.